Corporate governance, risk disclosure and cost of equity capital in the Malaysian public listed firms - Orojali Zadeh, Farahnaz (2015)
Risk disclosure has received considerable attention in today’s business world. However, there is a lack of research on the practices and trends of risk disclosure. Therefore, there is a need to examine the trend of risk disclosure over years as well as the determinant and consequence of risk disclosure. In particular, this study examined risk disclosure level, the influence of corporate governance on the risk disclosure level, and the impact of risk disclosure level on cost of equity capital. The secondary data for the study were based on annual reports, DataStream and Capital IQ of firms from non-financial firms listed on the Main Board of Bursa Malaysia from 2001 to 2011. Level of disclosure was measured using content analysis. Two empirical analyses were examined using multiple regressions. The content analysis findings confirmed a trend toward greater levels of risk disclosure. Firms disclosed risk on financial, non-financial and risk management framework respectively. Most of the information disclosed is either neutral or good, while bad news was infrequently reported. Firms risk disclosure also includes both monetary and non-monetary disclosures and firms tend to report more information about past risks rather than future risks. The results of the first empirical analysis show the significant and positive relationship between board size, independent non-executive directors, and audit committee independence with risk disclosure level but there is no significant relationship with ownership structure and race of the chairman. The second empirical analysis suggests firms with high level of risk disclosure will yield lower cost of equity capital. Overall, findings are consistent with political cost theory, agency theory, capital need theory and signaling theory. The findings have shown the importance of risk disclosure practices and it is recommended that policy makers, authorities and boards of directors to consider the disclosure of risk in a firm’s annual reports as a priority.